The Role Of Social Media Marketing In Enhancing Brand Image - An Analytical Study - - Boulahbel, Asmaa; Ghrieb, Taoues (khazzartech الاقتصاد الصناعي, 2023)
This study tries to determine the role of social media marketing (interaction, trendiness, customization, entertainment and E-WOM). To enhance the brand image at Ooredoo, The questionnaire served as a tool for data collection. , where a purposive sample of 276 was taken. The study concluded that there is a contribution and an impact of the different dimensions of marketing through social media in the improvement of the brand image among customers of the company by 56.5%, and the research suggested enhancing the company's social media pages to make them more uplifting and help them build a great reputation with the target audience. Therefore, the effect is at long term.